Dosimetric Characteristics of a Two-Dimensional Diode Array Detector Irradiated with Passively Scattered Proton Beams - Liengsawangwong, Praimakorn (Cancers (Basel), 2015)
Purpose: To evaluate the dosimetric characteristics of a two-dimensional (2D) diode array detector irradiated with passively scattered proton beams. Materials and Methods: A diode array detector, MapCHECK (Model 1175, Sun Nuclear, Melbourne, FL, USA) was characterized in passive-scattered proton beams. The relative sensitivity of the diodes and absolute dose calibration were determined using a 250 MeV beam. The pristine Bragg curves (PBCs) measured by MapCHECK diodes were compared with those of an ion chamber using a range shift method. The water-equivalent thickness (WET) of the diode array detector’s intrinsic buildup also was determined. The inverse square dependence, linearity, and other proton dosimetric quantities measured by MapCHECK were also compared with those of the ion chambers. The change in the absolute dose response of the MapCHECK as a function of accumulated radiation dose was used as an indicator of radiation damage to the diodes. 2D dose distribution with and without the compensator were measured and compared with the treatment planning system (TPS) calculations. Results: The WET of the MapCHECK diode’s buildup was determined to be 1.7 cm. The MapCHECK-measured PBC were virtually identical to those measured by a parallel-plate ion chamber for 160, 180, and 250 MeV proton beams. The inverse square results of the MapCHECK were within ±0.4% of the ion chamber results. The linearity of MapCHECK results was within 1% of those from the ion chamber as measured in the range between 10 and 300 MU. All other dosimetric quantities were within 1.3% of the ion chamber results. The 2D dose distributions for non-clinical fields without compensator and the patient treatment fields with the compensator were consistent with the TPS results. The absolute dose response of the MapCHECK was changed by 7.4% after an accumulated dose increased by 170 Gy. Conclusions: The MapCHECK is a convenient and useful tool for 2D dose distribution measurements using passively scattered proton beams. Variations in MapCHECK’s dose response with increasing levels of total accumulated radiation dose should be carefully monitored.